Synthesis of antifungal imines as inhibitors of ergosterol biosynthesis - Joydeep Karan; Aditi Kundu; Robin Gogoi; Kanchikeri Math Manjaiah; Ashutosh Kumar Singh; Koyel Mondal; Rajesh Kumar; Parshant Kaushik; Priya Saini; Virendra Singh Rana; Najam Akhtar Shakil (Journal of Taibah University for Science, 2025)
Ensuring a safe and secure supply of nutritious food for the ever growing global population necessitates the development of new eco-friendly fungicides to increase global food output by minimizing plant disease losses. Because of their broad biological relevance, imines are a promising target for fungicide development. To optimize the structure of imine derivatives for improved antifungal activity, twenty-seven Schiff bases derived from halogen-substituted benzenamines were prepared and characterized using spectral analysis in the present study. These compounds were investigated further for their in-vitro antifungal bio-efficacy against Rhizoctonia solani and Macrophomina phaseolina. Most of the compounds were effective against the test fungi with EC50 values ranging from 0.99 to 190.51 μg/mL. The substitution of chlorine at the phenyl ring attached to the carbon of the imine group resulted in the highest antifungal activity against both test fungi. The most effective antifungal compounds displayed >80% inhibition of the lanosterol-14α-demethylase enzyme.